Vulnerability of elderly consumers - their children’s perception - Balázs, Katalin; Vincze, Petronella; Hujber-Mitru, Szilvia (Magyar Gerontológia, 2022)
The research goal was studying elderly individuals’ consumer vulnerability in an unusual way. This is a topical issue, as for example the high prevalence of grandparent scams and other older adult-focused criminal activities is well known in the literature (e.g., AARP Foundation, 2003; Boush & mtsai, 2009; Yip & Schweitzer, 2015; Valant, 2015). A broad spectrum of studies (e.g., Carpenter & Yoon, 2017; Lee & Geitsfied, 1999; Peters et al., 2007) focuses on the aging consumer’s features that can be blamed for their vulnerability, as for example changes in cognitive capacity, fast speech processing and openness for social contact. The novelty of the present study is two-folded. First, a psychological approach was followed focusing on the role of persuasion knowledge (Friestad & Wright; 1994) and self-efficacy (Bandura, 1994) in this context. Second, not the elderly population, but their children’s perception was investigated in a mixed-method study.